Electron spin ecgo investigations on trapped epr active centers in oxygen contaminated polyacetylene - Nha, Nguyen Van; Bao Ngoc, Nguyen Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 12 No 4, 1996)
Abstract